Effect of high‐dose vocal fold injection of cidofovir and bevacizumab in a porcine model. (25th July 2016) - Ahmed, Mostafa. M.; Connor, Matthew. P.; Palazzolo, Mitzi; Thompson, Michelle E.; Lospinoso, Josh; O'Connor, Peter; Howard, N. Scott; Maturo, Stephen. C.
Abstract : Objectives: Perform a follow‐up study to investigate the histologic impact of high‐dose intralaryngeal cidofovir injections in porcine vocal cords, either alone or in combination with bevacizumab, and compared to saline controls. Study Design: This was an in vivo study involving 24 pigs with blinded pathologist review of specimens. Six groups were created, with four subjects in each group. Each subject received 10 or 20 mg of either cidofovir or bevacizumab alone, or in combination, injected into the right vocal cord. The left vocal fold was used as a saline control. Three separate injections were made at 2‐week intervals. Larynges were harvested at 8 and 12 weeks, stained with hematoxylin and eosin and trichrome stain, and reviewed for histologic changes by two blinded pathologists. Results: Minimal inflammation, edema, and atypia were noted with all treatments. Increased glandular inflammation was noted with 10 mg bevacizumab ( P < 0.05), which decreased when combined with 10 mg cidofovir ( P < 0.05). No lamina propria or muscle fibrosis was observed. Drug duration had no statistically significant histologic impact. Conclusion: High‐dose cidofovir and bevacizumab do not induce detrimental vocal fold changes. Combination cidofovir and bevacizumab do not cause vocal fold scarring. Further work is needed to assess systemic concentration with this high‐dose combination in humans. Level of Evidence: N/A. Laryngoscope, 127:671–675, 2017